Personality trait development at the end of life Antecedents and correlates of mean-level trajectories. [article]. - Wagner, Jenny
Empirical evidence over the past 20 years has documented that key aspects of personality traits change during adulthood. However, it is essentially an open question whether and how traits change at the very end of life and what role health, cognitive performance, perceived control, and social factors play in those changes. To examine these questions, we applied growth models to 13-year longitudinal data obtained from now-deceased participants in the Berlin Aging Study (N = 463; age at baseline M = 85.9 years, SD = 8.4; 51% men). Results revealed that neuroticism, on average, increases (about 0.3 SD in the last 10 years) and that this increase becomes even steeper at the end of life. In contrast, extraversion and openness decline rather steadily at the end of life (about -0.5 SD in the last 10 years). Additionally, poor health manifested as a risk factor for declines in extraversion and openness late in life but not neuroticism. Similar to earlier phases of life, better cognitive performance related to more openness. More loneliness was associated with higher neuroticism, whereas more social activity was associated with higher levels of extraversion and openness. Intriguing additional insights indicated that more personal control was associated with higher levels of extraversion and openness, whereas the feeling that one's life is controlled by others was associated with higher neuroticism but also with higher openness closer to death. We discuss potential pathways by which health, cognitive performance, control, and social inclusion resources and risk factors affect personality development late in life. -- (from the authors)